CHALLENGES AND SOLUTIONS TO THE USE OF ONLINE SHOPPING APPLICATIONS IN THE PERSPECTIVE OF ISLAMIC ECONOMYIN INDONESIA - Zuwardi; Azzahratul Hasanah, Musdeki Mulya, Riana Wiliza, Anita Triana, Sirtia Pelanda Onesti (Adisam Publisher, 2024)
The use of online shopping applications has become a predominant trend among the Indonesian population, presenting challenges and opportunities within the context of Islamic economics. This article discusses the challenges faced by users of online shopping applications from the perspective of Islamic economics in Indonesia, highlighting aspects such as Sharia compliance, transparency, and social responsibility. Challenges include the ambiguity of the halal status of products, uncertainty in transaction processes, and ethical issues related to promotions and advertisements. Simultaneously, this article identifies solutions that can be implemented to address these challenges. These solutions encompass the development of clear Sharia guidelines for online products and services, increased transparency in business processes, and enhanced awareness and education of the public regarding Islamic economic principles. The implementation of blockchain technology and Sharia-compliant payment mechanisms is also highlighted as potential solutions to improve trust and Sharia compliance within the online shopping ecosystem. Through this analysis, the article provides insights into how online shopping applications can be integrated with Islamic economic values, creating an ecosystem that is not only technologically innovative but also aligned with the principles of Islamic finance. Consequently, it is hoped that a more inclusive, transparent, and Sharia-compliant online shopping ecosystem can be established in Indonesia.